2018
DOI: 10.1007/s00705-018-3824-8
|View full text |Cite
|
Sign up to set email alerts
|

Host serum microRNA profiling during the early stage of foot-and-mouth disease virus infection

Abstract: Foot-and-mouth disease virus (FMDV) causes a highly contagious infection in cloven-hoofed animals, with many outbreaks in the developing world. MicroRNAs (miRNAs) are non-coding RNAs that regulate antiviral defence by post-transcriptional regulation of gene expression. In this study, the host miRNA response following FMDV infection was investigated in cattle, a natural host for FMDV. A significant alteration in serum miRNA expression was detected at early stages of infection. Compared to prior to infection, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Further, antiviral effect of host miR-203a mimics against FMDV was reported previously (Gutkoska et al, 2017). We have recently shown that transient expression of host miRNAs appears to target FMD virus genomic RNA in cell culture (Basagoudanavar et al, 2018). Also, other studies have shown inhibitory effect of artificial miRNAs (amiRNAs) on FMDV, by targeting either the IRES sequence in the 5'-UTR, or 3'-UTR or the 3D polymerase (Chang et al, 2014;Du et al, 2011;Gismondi et al, 2014).…”
Section: Introductionmentioning
confidence: 73%
“…Further, antiviral effect of host miR-203a mimics against FMDV was reported previously (Gutkoska et al, 2017). We have recently shown that transient expression of host miRNAs appears to target FMD virus genomic RNA in cell culture (Basagoudanavar et al, 2018). Also, other studies have shown inhibitory effect of artificial miRNAs (amiRNAs) on FMDV, by targeting either the IRES sequence in the 5'-UTR, or 3'-UTR or the 3D polymerase (Chang et al, 2014;Du et al, 2011;Gismondi et al, 2014).…”
Section: Introductionmentioning
confidence: 73%
“…However, the magnitude of the antiviral effect of the 8 miRNA mimics was observed to be varying. This could be attributed to the difference in the degree of sequence-specific miRNA interactions with viral elements as reported previously 31,33 and depends on the concentrations of miRNAs and targets. Further, the results of the experimental validation of all the considered 8 host miRNAs also supported the in silico predictions by more or less reducing the viral replication.…”
Section: Discussionmentioning
confidence: 57%
“…The study of anti-FMDV miRNAs in Bos taurus revealed 12 mature miRNAs (8 from miRBase www.nature.com/scientificreports/ and 4 from VIRmiRNA databases) having a total of 284 targets in 98 distinct FMDV genomic sequences, which suggests the possible existence of miRNA based anti-FMDV mechanism in Bos taurus to defend the FMDV. Viable miRNA targets have been identified by researchers worldwide with high reliability through miRNA profiling efforts that have been conducted with FMDV infected pigs and cattle 31,32 . This has inspired us to experimentally validate a handful of host miRNAs for their anti-FMDV properties.…”
Section: Discussionmentioning
confidence: 99%
“…• Severe disease and higher mortality has been seen in the male sex (Goyal et al, 2020;Zheng et al, 2020). Testing certain asymptomatic individuals may also be important for infection control purposes (for e.g., in congregate settings where COVID-19 cases have been identified, prior to time-sensitive surgical procedures, and prior to time-sensitive aerosol-generating procedures if PPE (personal protective equipment) supplies are limited, and in hospitalized patients at locations where prevalence is high (McIntosh, 2020).…”
Section: Historymentioning
confidence: 99%